Molecular prenatal diagnosis of megalencephalic leukoencephalopathy with subcortical cysts in a child from southwest of Iran. Issue 2 (26th November 2014) - Shariati, Gholamreza; Hamid, Mohammad; Saberi, Alihossein; Andashti, Behnaz; Galehdari, Hamid
Key Clinical Message Megalencephalic leukoencephalopathy (MLC) is a rare neurological disorder with an autosomal recessive pattern. Clinical diagnosis was based on macrocephaly, recurrent seizure, and magnetic resonance imaging (MRI). Here we report first finding of a novel homozygous single base deletion in the MLC1 gene in an affected Iranian child causing a premature stop codon (p.L150fs.160X).